BIOLOGICAL FEATURES OF GROWTH, DEVELOPMENT AND PRODUCTIVITY INDICATORS OF ANIMALS OBTAINED FROM CROSSING OF CATTLE OF DIFFERENT BREEDS - Цвігун, А. Т.; Шуплик, В. В.; Каспров, Р. В.; Щербатюк, Н. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The results of research on the biological features of growth, development and productivity of animals obtained from crossbreeding of cattle of different origins are presented. The aim of the research was to study the biological features of growth, development and productivity indicators in local animals of cattle obtained from crossing dairy cows with meat bulls. The research was conducted through research and production experiments, groups were formed on the principle of pairs of analogues. It was found that local animals at birth had a higher live weight compared to purebreds. The only exceptions are crossbreeds with Aberdeen Angus. The advantage in live weight in domestic animals was: the second group - 72.6 kg, or 16.9%; third - 62.6 kg, 14.6%; fourth - 87.4 kg, 20.4%; fifth - 66.1 kg, 15.4%; sixth - 30.7 kg, 7.1%. Between six and nine months, the average daily gain in domestic animals was higher except for the sixth group. The advantage was in the second group +100 g, in the third +227 g, in the fourth +159 g, in the fifth +111 g, and in animals of the sixth group the lag was -164 g. In the subsequent periods of cultivation local bulls prevailed. purebred according to this indicator. For the entire period of cultivation, from birth to 18 months, the advantage was the second group of 119 g, the third - 118 g, the fourth - 154 g, the fifth - 112 g, the sixth - 28 g. There are also differences in indicators measurements among animals of different groups, so the largest oblique length of the torso and chest girth had crossbreeds of the second and fourth groups, and the smallest of the third group. Similar results were obtained by latitudinal measurements. Analysis of data on linear growth and body structure indices indicate good development of animals and fairly harmonious body shapes. However, the differences between purebred animals and crossbreeds are observed and quite significant. The highest pre-slaughter weight was in animals of the second group of 500.7 kg. (+78.8 kg.). A similar situation is observed in terms of slaughter mass. The largest slaughter weight was obtained from animals of the fifth group 319.3 kg. (+83 kg). The animals of the fifth group also had the heaviest carcasses of 310.1 kg (+79 kg).